Influence of Standard Tannin and Standard Saponin on Methane Mitigation and Rumen Fermentation Characteristics for Ruminants - A, Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Methane is one of the important green house gas, which is normally emitted fromruminants and represents a loss of feed energy by 8-12 per cent. A huge number of feedingstrategies are used to mitigate the methane emission from ruminants for sustainable animalproduction. Hence an experiment was conducted to study the influence of standard tannin (ST)and standard saponin (SS) on methane mitigation and rumen fermentation characteristicsfor ruminants by in vitro gas production technique (IVGPT). The IVGPT was carried outby incubating the Cumbu Nappier hybrid (CN-CO4) grass and rumen liquor with ST + SSat varying levels viz., 0, 1.03 per cent + 0.78 per cent, 2.06 per cent + 1.56 per cent, 3.09per cent + 2.34 per cent and 4.12 per cent + 3.12 per cent of substrate in six replicates fora period of 24 hours in shaking water bath. After 24 hours the total gas production and pHwere measured and methane was estimated in Gas Chromatography. The in vitro true drymatter digestibility (IVTDMD) was estimated and methane emission (ml) per 100 mg trulydigested substrate was calculated. The rumen fermentation characteristics were also studied.The total gas production was significantly (p